Inhibitory Activity of Boesenbergia rotunda (L.) Mansf. Rhizome towards the Expression of Akt and NF-KappaB p65 in Acetic Acid-Induced Wistar Rats. (20th May 2020) - Rosdianto, Aziiz Mardanarian; Puspitasari, Irma Melyani; Lesmana, Ronny; Levita, Jutti
Abstract : Ethnopharmacological Relevance . Boesenbergia rotunda has been traditionally used to reduce stomach discomfort in Indonesia. The objective of the present study was to investigate the anti-inflammatory mechanism and acute toxicity of the ethanol extract of B. rotunda rhizome (BREE) in Wistar rats. Materials and Methods . Forty-eight male Wistar rats were divided into anti-inflammatory mechanism study ( n = 18) and acute toxicity study ( n = 30). The anti-inflammatory mechanism study employed six groups ( n = 3), e.g., the normal control, negative control, positive control (quercetin 20 mg/kg BW), and three doses of BREE (250 mg/kg BW; 500 mg/kg BW; 1000 mg/kg BW). All groups (except the normal control) were inflammatory-induced i.p. using 0.1 mL of 1% of acetic acid. The expression of Akt and NF-kappaB p65 in the stomach and intestine of the rats was examined using Western blot analysis. The acute toxicity study (21 days) was conducted by following the Regulation of Indonesia National Agency of Drug and Food Control No. 7/2014 about In Vivo Nonclinical Toxicity Study using 5 doses of BREE (250 mg/kg BW; 500 mg/kg BW; 1000 mg/kg BW; 2000 mg/kg BW; 4000 mg/kg BW). Results . BREE reduces the infiltration of inflammatory cells in both the stomach and the intestine of acetic acid-induced rats. BREE also alters the expression of Akt and NF-kappaB p65 in the rat's stomach and intestine (p = 0.005 ). The acute toxicity study reveals no lethal effects and behavioral signs of toxicity at all tested doses, which indicates that the LD50 is greater than 4000 mg/kg BW. Conclusion . Taken together, BREE could inhibit the expression of Akt and NF-kappaB p65 in the stomach and intestine of acetic acid-induced Wistar rats. This plant could be further explored for its potential as plant-based antistomach ulceration.